INTRODUCTION - Bulan, Ramy; Crook, Peter (Journal of Malaysian and Comparative Law, 1998)
This special issue of the Journal of Malaysian and Comparative Law is devoted to the proceedings of the conference, "Legal Pluralism: The Role of Customary Law in Preserving Indigenous Heritage", sponsored by the Faculty of Law, University of Malaya in conjunction with the Majlis and Adat Istiadat of Sarawak and the Office of the Chief Registrar, Native Courts Sarawak, held in Kuching, Sarawak on November 11-12, 1997.